Plaque Distribution of Basilar Artery Fenestration by 3D High-Resolution MR Vessel Wall Imaging. Issue 7 (July 2019) - Liu, Lei; Zhang, Xue-Bin; Lu, Shuo; Liu, Zun-Jing; Zhu, Xian-Jin
The association between fenestrations and neurovascular pathology is not well defined. The morphology of vessel wall plays an important role in the development of neurovascular pathology. We sought to explore the plaque distribution around basilar artery fenestration (BAF) by three-dimensional high-resolution MR vessel wall imaging (3D HRMRI). Patients with BAF on 3D HRMRI images were enrolled. All cross-sectional slices of basilar arteries were assessed and categorized based on the location of fenestration as proximal segment, in-bifurcation segment, and distal segment. Furthermore, plaques in the in-bifurcation segment were classified according to their orientation being centered on the lateral, interior, dorsal, or ventral wall of the vessel. In all, 12 cases with BAF involving 661 cross-sectional image slices in entire basilar arteries were included. Plaques were found in 190 image slices, with the distribution of 41 slices in the proximal segment, 144 slices in the in-bifurcation segment and 67 slices in the distal segment. Plaques were found more frequently in the proximal and in-bifurcation segments than in the distal segment ( P < 0.001), but there was no statistical difference between the proximal and in-bifurcation segment ( P = 0.11). In the in-bifurcation segment, plaques were more frequently located at the lateral (50.0%) than other interior (16.0%), dorsal (21.0%), and ventral (13.0%) wall ( P < 0.001).Plaques of BAF tend to locate in the proximal and in-bifurcation segments, especially at the lateral wall of the in-bifurcation segment.